Short-term recovery pattern of plasma fibrinogen after cardiac surgery: A prospective observational study. - Gabor Erdoes; Wulf Dietrich; Monika Pia Stucki; Tobias Michael Merz; Anne Angelillo-Scherrer; Michael Nagler; Thierry Carrel; Balthasar Eberle (PLoS ONE)
Low plasma fibrinogen level is common after cardiopulmonary bypass (CPB). Current substitution practice with fibrinogen concentrate generally follows a single measurement and cut-off values from the literature, whereas early postoperative endogenous fibrinogen kinetics is incompletely described and widely disregarded. The aim of this study was to determine the short-term recovery pattern of plasma fibrinogen after CPB weaning. Our hypothesis was that in the absence of surgical bleeding, CPB-induced hypofibrinogenemia would resolve spontaneously and predictably within a few hours. In a prospective, observational study of 26 patients undergoing conventional CPB (cCPB) or minimally invasive extracorporeal circulation (MiECC), Clauss fibrinogen level (C-FIB) was determined at 10 closely spaced time points after protamine administration. Primary endpoint was the time to recovery of post-CPB fibrinogen levels to ≥1.5 g/L. C-FIB reached its nadir after protamine administration corresponding to 62 ± 5% (mean ± SD) of the baseline level after cCPB and 68 ± 7% after MiECC (p = 0.027 vs. cCPB). C-FIB recovered spontaneously at a nearly constant rate of approximately 0.08 g/L per hour. In all patients, C-FIB was ≥1.5 g/L at 4 hours and ≥2.0 g/L at 13 hours after CPB weaning. Following cardiac surgery with CPB and in the absence of surgical bleeding, spontaneous recovery of normal endogenous fibrinogen levels can be expected at a rate of 0.08 g/L per hour. Administration of fibrinogen concentrate triggered solely by a single-point measurement of low plasma fibrinogen some time after CPB is not justified.